2013
DOI: 10.1002/bies.201300059
|View full text |Cite|
|
Sign up to set email alerts
|

Retroviruses facilitate the rapid evolution of the mammalian placenta

Abstract: The mammalian placenta exhibits elevated expression of endogenous retroviruses (ERVs), but the evolutionary significance of this feature remains unclear. I propose that ERV-mediated regulatory evolution was, and continues to be, an important mechanism underlying the evolution of placenta development. Many recent studies have focused on the co-option of ERV-derived genes for specific functional adaptations in the placenta. However, the co-option of ERV-derived regulatory elements has the potential to co-opt ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 84 publications
0
73
0
Order By: Relevance
“…This plasticity may have been driven by evolutionary intraspecies tensions between the mother and the fetus and the involved genes. Likely, such tensions resulted in a field of opposing processes between the parent and offspring (often called "battlefield" or "arms race") that led to a very high degree of species-specific variation [15,17,95]. These selective pressures and evolutionary forces are regarded to be responsible for many pregnancy diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This plasticity may have been driven by evolutionary intraspecies tensions between the mother and the fetus and the involved genes. Likely, such tensions resulted in a field of opposing processes between the parent and offspring (often called "battlefield" or "arms race") that led to a very high degree of species-specific variation [15,17,95]. These selective pressures and evolutionary forces are regarded to be responsible for many pregnancy diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These selective pressures and evolutionary forces are regarded to be responsible for many pregnancy diseases. In consequence, a better understanding of the basic processes in various species will provide key insights into diseases of pregnancy in the human [17]. This is especially important, because relevant features of human placentation are present only in the great apes such as the chimpanzee and the gorilla, but ethical reasons strongly prohibited their usability for experimental approaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Do TEs rewire regulatory networks or does natural selection rewire networks using their promoters as handy components? TEs (including retroviruses) are suggested to have rewired endometrial and placental regulatory networks (Cohen et al 2009;Lynch et al 2011;Emera and Wagner 2012b;Chuong 2013;Chuong et al 2013). Although TE insertions can occur almost anywhere in the genome, including in crystallin genes (Nag et al 2007), their promoters have never been reported to confer lens-specific expression, or rewire regulatory networks of the lens, despite the recruitment of diverse genes as crystallins during vertebrate evolution (Wistow 2003).…”
mentioning
confidence: 99%